A study on the Effect of Telecollaboration through Social Networking on Reading Comprehension and Vocabulary Learning: The Case of Iranian Female High School EFL Learners - Mahnaz Azad; Maryam Kamarei (Journal of English Language Studies, 2021)
Technology enhanced instruction has been a paramount issue in recent decades leading to a shift in educational context. Moreover, telecollaboration as an electronically mediated intercultural communication has been introduced for the purpose of foreign language learning as well as the development of intercultural competence. Along this way, the present study was an attempt to probe on the effect of social networking through mobile assisted language learning (MALL) instruction (i.e., WhatsApp) on high school students’ reading comprehension and vocabulary learning. Furthermore, the difference between the effect of social networking through WhatsApp on the learners’ reading comprehension ability and vocabulary learning was compared. The design of the study was quasi-experimental with pre-test/post-test and the experimental and control groups. To do so, 60 female high school learners were homogenized using the Oxford Placement Test. Reading comprehension and vocabulary pre- and post-tests were administered among the learners to examine the effect of MALL instruction though WhatsApp on the learners’ reading comprehension and vocabulary learning. To analyze the data, independent samples t-test and MANOVA were used. Findings showed the outperformance of the experimental group over the control group in both reading comprehension and vocabulary learning. However, no statistically significant difference was found between the learners’ reading comprehension and vocabulary learning when they received social networking instruction through WhatsApp. Therefore, it can be concluded that using MALL can have beneficial effects on EFL learners’ reading comprehension and vocabulary.